JUST ONE THING - John Mauldin (John Wiley & Sons, Inc., 2006)
Investing is hardâ€”as hard as Chinese arithmetic, as another friend of mine used to say. Itâ€™s onerous, treacherous, humiliating, and subject to extreme weather conditions. My old partner Fred Kittler said it best: â€œThe stock market trades to inï¬‚ict the maximum amount of pain.â€ I donâ€™t know about you, but I have a very low threshold of pain. Yet I spent a career on Wall Street, ï¬rst as an analyst following volatile technology companies, as an investment banker, a venture capitalist, and ï¬nally running what ended up as a billion-dollar hedge fund. I did it by investing in the fog